2016
DOI: 10.1039/c6ta04196e
|View full text |Cite
|
Sign up to set email alerts
|

Facile hydrothermal synthesis of SnCoS4/graphene composites with excellent electrochemical performance for reversible lithium ion storage

Abstract: An SnCoS4/graphene composite with uniformly distributed SnCoS4 hybrid nanocrystals was prepared by a one-pot hydrothermal route and exhibits excellent electrochemical performance for reversible lithium storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 67 publications
3
15
0
Order By: Relevance
“…[6a, 22] The corresponding charge capacities of CNTs@C@CoS 2 and CNTs@CoS 2 for the first cycle are 996 and 875 mAh g À1 ,l eadingt ot he ac oulombic efficiency of 79.6 and 70.3 %, respectively.T he large capacity fading can be explained by the formation of SEI layer on electrode surface and the trapping of lithium inside the active material, which is common for metal sulfide anode materials. [23] After three cycles, the coulombic efficiency of CNTs@C@CoS 2 increases to 92 %. The cycle performance of the CNTs@C@CoS 2 and CNTs@CoS 2 are presentedi nF igure 4c at the currentd ensity of 0.2 Ag À1 .I tc an be seen that the discharge capacity of the CNTs@CoS 2 electrode drops to 751 mAh g À1 after 100 cycles.…”
Section: Resultsmentioning
confidence: 96%
“…[6a, 22] The corresponding charge capacities of CNTs@C@CoS 2 and CNTs@CoS 2 for the first cycle are 996 and 875 mAh g À1 ,l eadingt ot he ac oulombic efficiency of 79.6 and 70.3 %, respectively.T he large capacity fading can be explained by the formation of SEI layer on electrode surface and the trapping of lithium inside the active material, which is common for metal sulfide anode materials. [23] After three cycles, the coulombic efficiency of CNTs@C@CoS 2 increases to 92 %. The cycle performance of the CNTs@C@CoS 2 and CNTs@CoS 2 are presentedi nF igure 4c at the currentd ensity of 0.2 Ag À1 .I tc an be seen that the discharge capacity of the CNTs@CoS 2 electrode drops to 751 mAh g À1 after 100 cycles.…”
Section: Resultsmentioning
confidence: 96%
“…As ac onsequence, the electrochemical performances could be remarkably enhanced for applications in LIBs. [16][17][18] Many BMS materials,s uch as NiCo 2 S 4 , [19] Cu 2 SnS 3 , [20] CoSnS 4 , [21] MnCo 2 S 4 , [22] and Zn 0.76 Co 0.24 S, [23] have been investigated as anode materials for LIBs. For example, Yang et al designed 3D Zn 0.76 Co 0.24 Sn anoartichokes as anode material for LIBs, which exhibited ah igh capacity of 750 mA hg À1 at ac urrent density of 200 mA g À1 after 100 cycles.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Xia et al [5] synthesized NiCo 2 S 4 with conductivity about 100 times as high as that of NiCoO 4 .K ang et al [6] fabricated CoMoS 4 exhibiting the improvement on the electrochemical performance from the synergistic effect of the ternary metal sulfides. Xu et al [7] reported that SnCoS 4 /graphene hybrid showedl ower impedance and more excellent electrode reactionk inetics due to the hybrid nanocrystals with its unique structure and morphology.N evertheless, the applications of the TMSs anode are hampered for its structuralc racks, volumec hange, particle aggregation and capacityf ading during the delithiation/lithiation process. [8] To date, numerousr esearch attempts have been made to explore the possibilities to improvethe specific capacity,rate capability, and cycle stabilityo fL IBs.…”
Section: Introductionmentioning
confidence: 99%